MENCARI KALIMATUN SAWA DALAM PLURALISME AGAMA (KAJIAN DALAM PERSPEKTIF ISLAM) - Nuraeni, Nuraeni (Living Islam: Journal of Islamic Discourses, 2020)
Religious pluralism in Indonesia is a necessity that cannot be avoided because it adheres to diversity. As we know that in Indonesia there are six religions recognized by the government namely (Islam, Christianity, Hinduism, Hinduism, Buddhism, Catholicism and Kong hu chu) and every Indonesian citizen must embrace one of these religions, besides that human beings themselves are part of pluralism itself, so we live in pluralism.Normatively, doctrinaire of religion always teaches kindness, love and harmony. But sociological reality shows the opposite, religion is actually used as a source of ongoing conflict, both internal and external conflicts, such as clashes between the Early Church Christians with Jews, Christians with adherents of Roman religion (imperial religion) in the first century to the third century. Not much different from that in Indonesia, so we need to find a meeting point or Sawa sentence, looking for a conducive and prospective approach to the realization of sacred religious values (fundamental values) to be applicable solutions in looking at this plural future.